ANALYSIS OF PACKAGING DESIGN ON CONSUMER PREFERENCE OF FRUIT JUICE MANUFACTURING COMPANIES IN NAIROBI CITY COUNTY, KENYA - KIBATI, PETER; Erastus Thoronjo (IJRDO - Journal of Applied Management Science, 2021)
The study investigated packaging design on consumer preference of fruit juice manufacturing “companies in Nairobi City County, Kenya. It was guided by the accompanying specific objectives that are; to examine the extent to which packaging material has influenced consumer preference of fruit Juice manufacturing companies in Nairobi County, Kenya, to establish the extent to which packaging functionality has influenced consumer preference of fruit Juice manufacturing companies in Nairobi County, Kenya and to ascertain how packaging shape has influenced consumer preference of fruit Juice manufacturing companies in Nairobi County, Kenya. This examination was anchored by three research theories that are Theory of Reasoned Action (TRA), Consumer Utility Theory and Brand Equity Theory. The study used descriptive research design. Descriptive research design is suitable to utilize in light of the fact that the exploration searches out to build up the genuine circumstance in regards to packaging designs and consumer preference among fruit juice manufacturers. The study was completed in retail outlets situated in Nairobi City County. The populace for this research established all the retail outlets in Nairobi County completely enrolled and in operation. The objective populace and unit of analysis for this investigation were all the 804 representatives working in the retail outlet segment in Nairobi County. The unit of inquiry was the sales managers, accountants and merchandisers of retail outlets in Nairobi County, Kenya with a sample size of 267. From the information gathered on packaging material most of the participants of this research announced that the plastic packaging material is identified with the juice dinking shelf life. Also packaging material is related with consumer preference. In view of the discoveries, the participants of this research emphatically concurred that the vast majority of fruit juice package is easy to carry. Further the study found (R2) of 0.763 and which inferred that 76.3% is well and fits in the data. The study found positive correlation in packaging material, packaging functionality, packaging shape and consumer preference. In view of the research study it is recommended that juice manufacturing companies should consistently grasp packaging designs either from plastic packaging designs and can packaging designs; that are cylindrical shape, rectangular shape or oval shape designs; and are easier to carry and are re-usable after consumption. This study suggested study to be done on the elements of packaging designs in the Juice manufacturing companies in Kenya as whole. This will help to gain more knowledge on consumer Preference of packaging designs by juice manufacturing companies in the region where there is a larger population.